Sauer, Boas, Kroeber e a cultura superorgânica: notas sobre a relação entre geografia e antropologia - Breno Viotto Pedrosa (Confins)
In this article, we compare the thought of F. Boas and A. Kroeber, elucidating its general scheme of analysis, seeking the geographical features of his thinking and highlighting the elements that will be absorbed by Carl Sauer in his cultural geography. Furthermore, we tried to demonstrate the interrelationships between Ratzel’s thought, its influence in the context of Boas empiricist anthropology and, finally, the construction of the idea of ​​superorganic Kroeber.